Modelling of Fuel Cells and Related Energy Conversion Systems - Ilenia Rossetti (ChemEngineering, 2022)
Heat and power cogeneration plants based on fuel cells are interesting systems for energy- conversion at low environmental impact. Various fuel cells have been proposed, of which proton-exchange membrane fuel cells (PEMFC) and solid oxide fuel cells (SOFC) are the most frequently used. However, experimental testing rigs are expensive, and the development of commercial systems is time consuming if based on fully experimental activities. Furthermore, tight control of the operation of fuel cells is compulsory to avoid damage, and such control must be based on accurate models, able to predict cell behaviour and prevent stresses and shutdown. Additionally, when used for mobile applications, intrinsically dynamic operation is needed. Some selected examples of steady-state, dynamic and fluid-dynamic modelling of different types of fuel cells are here proposed, mainly dealing with PEMFC and SOFC types. The general ideas behind the thermodynamic, kinetic and transport description are discussed, with some examples of models derived for single cells, stacks and integrated power cogeneration units. This review can be considered an introductory picture of the modelling methods for these devices, to underline the different approaches and the key aspects to be taken into account. Examples of different scales and multi-scale modelling are also provided.